Polyaniline composite material as well as preparation method and application thereof
The polyaniline composite material constructed by nanofiberization and in-situ doping solves the problem of extracting bromine from low-concentration high-salinity brine in existing technologies, realizing efficient and environmentally friendly preparation of elemental bromine and material recycling, and is suitable for complex high-salinity brine systems such as seawater.
Patent Information
- Application Number
- CN202511356436.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies are difficult to effectively extract bromine from high-brine brine, especially when the Br- concentration is below 300 ppm, resulting in low bromine yield, high cost, complex process, and serious environmental pollution.
A polyaniline composite material with high specific surface area and high oxidation state density was constructed by nanofiberization and in-situ doping. As a microreactor, Br- was directly adsorbed from low-concentration high-halogen brine, and bromine was prepared simultaneously through catalytic oxidation and desorption, thereby realizing the activation and recycling of the polyaniline composite material.
It improves the adsorption capacity and yield of bromine, simplifies the process, reduces energy consumption and cost, and enables efficient extraction of elemental bromine from high-br-concentration brine with low Br- concentration. It is suitable for complex high-salinity brine systems such as seawater, seawater desalination tailwater, and salt lake brine.
Smart Images

Figure CN121372352A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of adsorbent technology, in particular to a polyaniline composite material and a preparation method and application thereof. BACKGROUND
[0002] Bromine is an important fine chemical raw material, which is widely used in medicine, pesticide, bactericide, refrigerant, electronic product, photosensitive material, flame retardant, fire extinguishing agent, oil exploitation and other industries and fields. At present, about 20% of the produced bromine comes from seawater, and the rest comes from salt lake brine and deep well brine. Whether seawater, seawater desalination tail water, salt lake brine, deep well brine or potassium fertilizer mine by-product water, they all belong to high-salinity brine, which contains various ions interference, among which chlorine and bromine are homologous elements, and the interference is large. In addition, the Br - concentration in high-salinity brine is low, <300 ppm, generally about 50-80 ppm, while the Cl - concentration in high-salinity brine is high, and the concentration ratio of chlorine to bromine is as high as 600-7500:1, and the bromine concentration is much lower than that of chlorine, which further brings great difficulty to the extraction and preparation of bromine from high-salinity brine.
[0003] At present, the main method for producing bromine is to first oxidize Br - in high-salinity brine into bromine element by using chlorine, electrochemistry, H2O2, etc., and then to adsorb and capture the bromine element by using antioxidant resin or silver salt. However, this method requires that the Br - concentration in high-salinity brine be >300 ppm, otherwise the yield of bromine element will be greatly reduced and the cost will be greatly increased. However, the Br - concentration in most high-salinity brine is much lower than 300 ppm, which cannot meet the requirement. In addition, this method has great corrosion to equipment, and the equipment investment is large, the process is complex, and the energy consumption is high. In addition, after adsorbing and capturing the bromine element, chemical reagents are needed to desorb the bromine, and then another method is needed to recover the bromine element, which is a complicated process. In addition, the yield, purity and production cycle of bromine element are long, and waste liquid is generated to pollute the environment. SUMMARY
[0004] Based on the technical problems existing in the background technology, the present application provides a polyaniline composite material and a preparation method and application thereof. The present application constructs a specific microstructure with high specific surface area and high oxidation state density through nanofiberization and in-situ doping, so that it itself becomes a “micro-reactor”. The high-salinity brine with low Br - concentration is directly used as raw material, which has good adsorption performance for Br - , greatly improves the adsorption amount of Br - , and synchronously oxidizes and desorbs, so as to realize the synchronous preparation of bromine element and activated polyaniline composite material, fill the technical blank in the bromine production industry, and provide a new high-salinity brine bromine extraction method which can be industrialized.
[0005] This invention proposes a polyaniline composite material, comprising: a carrier, iron, and polyaniline; wherein the iron has an Fe2O3 layer on its surface, the iron is uniformly distributed on the surface of the carrier, the polyaniline coats the carrier and the iron, and the polyaniline is in the form of nanofibers.
[0006] The Fe2O3 layer on the iron surface can be distributed continuously or in a discontinuous or dispersed manner.
[0007] Preferably, the nanofibers have fluffy protrusions on their surface; the fluffy protrusions can further increase the specific surface area of the polyaniline composite material and further improve its adsorption performance.
[0008] Preferably, the nanofibers are interwoven.
[0009] Preferably, the polyaniline in the polyaniline composite material is in the form of PANI. + state.
[0010] PANI + The salt state, also known as the Emeraldine salt state, is an oxidized form of polyaniline (PANI) and has unique electrical conductivity and chemical stability.
[0011] This invention constructs a polyaniline composite material with high specific surface area, high oxidation state density, and specific microstructure through nanofiberization and in-situ doping;
[0012] The specific microstructure of polyaniline composites makes them resistant to Br. - It exhibits excellent selective adsorption, even in Br - very low concentration, Cl - Even in highly concentrated brine with a high concentration of chlorine and bromine, the Br content remains very high. - It exhibits excellent adsorption performance, high adsorption capacity, and maintains good selective adsorption, enabling the adsorption of low Br⁻ from... - Large-scale adsorption and extraction of Br in high-concentration brine - Increase yield; and Fe, Fe2O3 and PANI + The phase-state combination makes it a "microreactor" in itself, possessing catalytic oxidation capabilities. It can combine with oxidants or electrolytic oxidation to react with Br. - Catalytic oxidation to elemental bromine, and simultaneously the generation of elemental bromine, the elemental bromine desorbs from the polyaniline composite material, thereby activating the polyaniline composite material and enabling it to be recycled.
[0013] Preferably, the nanofibers have a length of 1-10 μm and a diameter of 10-100 nm.
[0014] Preferably, the nanofibers have a length of 3-7 μm and a diameter of 50-90 nm.
[0015] Preferably, the specific surface area of the polyaniline composite is 300-1200 m 2 / g; more preferably, 600-1200 m 2 / g.
[0016] Preferably, the particle size of the iron is 0.1-0.5 mm; more preferably, 0.2-0.3 mm.
[0017] In the polyaniline composite, the weight ratio of the iron and the polyaniline can be 0.001-0.5:0.5-10.
[0018] Preferably, the carrier has adsorption performance.
[0019] Preferably, the specific surface area of the carrier is ≥300 m 2 / g; more preferably, 600-1200 m 2 / g.
[0020] Preferably, the carrier has a porous structure or / and a layered structure.
[0021] Preferably, the carrier comprises one or more of a porous material, graphene, a carbon nanotube, and a layered double hydroxide.
[0022] Preferably, the porous material comprises one or more of a one-dimensional porous material, a two-dimensional porous material, and a three-dimensional porous material.
[0023] Preferably, the porous material comprises one or more of a porous carbon fiber, a porous carbon particle, a porous carbon cloth, a porous carbon felt, a molecular sieve, a porous silicon fiber, a porous silicon particle, a porous silica fiber, a porous silica particle, a porous titanium dioxide fiber, a porous titanium dioxide particle, a porous ceramic, an aerogel, and a sponge.
[0024] The shape and size of the carrier are not limited, for example, the carrier can be a porous fiber, can be a zeolite molecular sieve particle, can be a cylindrical porous material with a length of 0.5-2 cm and a diameter of 0.1-5 mm, can be a porous carbon cloth, can be a porous ceramic tube, an aerogel, etc.
[0025] The material of the above-mentioned porous ceramic is not limited, and the ceramic material can be SiC, boron nitride, alumina, silicon nitride, etc.
[0026] The above-mentioned molecular sieve can be a zeolite, MOF-5, COF-1, ZIF-8, etc., and the above-mentioned aerogel can be a graphene aerogel, etc.
[0027] Preferably, when the carrier has a porous structure, the pore size is 0.3-100 nm; more preferably, 70-100 nm.
[0028] The pores in the porous material include one or more of mesopores, micropores, and macropores.
[0029] The application further provides a preparation method of the polyaniline composite material, comprising the following steps: uniformly mixing a carrier, iron powder, and aniline, standing, adding an initiator solution to perform a polymerization reaction, and obtaining the polyaniline composite material.
[0030] Preferably, the weight ratio of the carrier, the iron powder, and the aniline is 100:0.001-0.5:0.5-10.
[0031] Preferably, the weight ratio of the aniline and the initiator is 1:0.8-1.5.
[0032] Preferably, the concentration of the initiator solution is 0.1-3 mol / L, and more preferably 0.1-1 mol / L.
[0033] The initiator is preferably a persulfate salt, such as ammonium persulfate, potassium persulfate, sodium persulfate, or the like.
[0034] Preferably, the standing is performed at room temperature for 1-5 h.
[0035] Preferably, the polymerization reaction is performed at room temperature.
[0036] The room temperature refers to 5-35 ℃, and more preferably 20-30 ℃.
[0037] Preferably, after the standing, the initiator solution is added dropwise to perform the polymerization reaction.
[0038] Preferably, the dropping speed is 1-2 drops / s.
[0039] In the preparation method, after the standing, the initiator solution is added dropwise, and the polymerization reaction is performed simultaneously.
[0040] The total reaction time is 5-10 h, starting from the time when the initiator solution is added dropwise.
[0041] After the polymerization reaction is completed, solid-liquid separation, washing, and drying are performed to obtain the polyaniline composite material.
[0042] The polyaniline composite material with a specific structure is successfully prepared by adjusting the raw material ratio and the process parameters.
[0043] The application further provides the application of the polyaniline composite material and the polyaniline composite material prepared by the method in selective adsorption of bromide ions and preparation of bromine by catalytic oxidation.
[0044] Preferably, the application is in selective adsorption of bromide ions in high-halogen salt water.
[0045] Preferably, the Br- concentration in the high-halogen salt water is ≤300 ppm. - Preferably, the Br- concentration in the high-halogen salt water is ≤300 ppm.
[0046] Preferably, the concentration ratio of chlorine and bromine in the high-halogen brine is 600-7500:1.
[0047] Preferably, the high-halogen brine is one of seawater, seawater desalination tail water, salt lake brine, deep well brine, and byproduct water of potassium fertilizer mine.
[0048] Preferably, the bromine element is prepared by catalytic oxidation in an acidic environment.
[0049] Preferably, the pH of the acidic environment is ≤3.
[0050] Preferably, the acidic environment is maintained by an organic acid.
[0051] Preferably, the organic acid is one or more of formic acid, acetic acid, propionic acid, butyric acid, lactic acid, citric acid, malic acid, tartaric acid, oxalic acid, benzoic acid, salicylic acid, phthalic acid, terephthalic acid, acrylic acid, methacrylic acid, sorbic acid, fumaric acid, maleic acid, succinic acid, and glutaric acid.
[0052] The present application also provides a method for preparing bromine element from high-salinity brine, comprising method A or method B,
[0053] Method A comprises the following steps: adsorbing bromine in high-salinity brine by polyaniline composite material, then eluting the adsorbed bromine in the polyaniline composite material by eluent to obtain desorption liquid; blowing bromine vapor from the desorption liquid and condensing to obtain liquid bromine element;
[0054] Method B comprises the following steps: adsorbing bromine in high-salinity brine by polyaniline composite material, then using the polyaniline composite material adsorbing bromine as an anode to perform electrolytic desorption in an acidic aqueous solution to obtain desorption liquid; blowing bromine vapor from the desorption liquid and condensing to obtain liquid bromine element;
[0055] In method A, the eluent is an acidic aqueous solution containing an oxidizing agent.
[0056] The polyaniline composite material is the above-mentioned polyaniline composite material or the polyaniline composite material prepared by the above-mentioned method.
[0057] In the above-mentioned method A, the specific microstructure of the polyaniline composite material makes it have high selectivity and high adsorption capacity for Br - , and can adsorb a large amount of Br - from high-halogen brine with low Br - concentration, thereby improving the yield; and the polyaniline composite material itself becomes a "micro-reactor" and has catalytic oxidation effect, so that it can activate the oxidizing agent, oxidize Br - to Br·, and then form Br2, which is desorbed from the polyaniline composite material, and Br2 and Br -Coordination to form Br - 3 is dissolved in the desorption solution.
[0058] In the above method B, the polyaniline composite material adsorbs Br - from the high-halogen salt water in a large amount at a low Br - concentration; then, as the positive electrode, a voltage is applied to electrolytically oxidize Br - to Br·, and further to Br2, which is desorbed from the polyaniline composite material, and Br2 and Br - coordinate to form Br - 3.
[0059] In the above method A and method B, hot air can be used to blow bromine vapor from the desorption solution.
[0060] In the above method A and method B, bromine in the desorption solution exists in the form of Br3 - , Br2 and Br - , mainly in the form of Br3 - ; hot air is blown to the desorption solution, and Br3 - and Br2 in the desorption solution are evaporated into bromine vapor, separated from the desorption solution, and then condensed to obtain liquid bromine, which is simple in operation and pollution-free.
[0061] In the above method A, the polyaniline composite material can be made into a chromatographic column as a filler, high-salt brine is loaded, bromine is adsorbed, and then an eluent is used for elution to obtain a desorption solution.
[0062] In the above method B, the polyaniline composite material can be directly added to high-halogen salt water for adsorption, or the polyaniline composite material can be made into a roll-shaped film and injected into high-halogen salt water for filtration; then, electrolytic analysis is performed.
[0063] Preferably, in method A, the pH of the eluent is ≤3; more preferably, the pH is 2-3.
[0064] Preferably, in method A, the oxidant is one or more of oxygen, ozone, potassium permanganate, nitric acid, concentrated sulfuric acid, persulfate, hydrogen peroxide, sodium peroxide, sodium hypochlorite, calcium hypochlorite, chlorine, potassium dichromate, lead dioxide, chromium trioxide, perchloric acid, periodate acid, osmium tetroxide, and sodium dichloroisocyanurate.
[0065] The concentration of the oxidant in the above eluent is not limited, which can be a low concentration such as 0.0001 mol / L or a saturated concentration.
[0066] Preferably, in method B, the pH of the acidic aqueous solution is ≤3; more preferably, the pH is 2-3.
[0067] The pH of the above acidic aqueous solution is determined using an organic acid; the organic acid is one or more of the following: formic acid, acetic acid, propionic acid, butyric acid, lactic acid, citric acid, malic acid, tartaric acid, oxalic acid, benzoic acid, salicylic acid, phthalic acid, terephthalic acid, acrylic acid, methacrylic acid, sorbic acid, fumaric acid, maleic acid, succinic acid, and glutaric acid.
[0068] The material of the negative electrode is not limited; it can be carbon rod, Pt, graphite, etc.
[0069] Preferably, in method B, the voltage of electrolysis is ≤1.2V; more preferably, the pH is 1.05-1.2V.
[0070] In method B above, the electrolysis time is 5-20 min; more preferably 5-15 min.
[0071] In method B above, selecting a suitable voltage range can fully utilize Br - Oxidation to Br2 can lower the voltage below the peroxidation threshold of polyaniline, preventing the polyaniline composite material from being "over-doped" and improving the cycle life of the polyaniline composite material; the cycle life of the polyaniline composite material in method B is an order of magnitude higher than that in method A.
[0072] In methods A and B above, the bromine desorption rate is ≥94%, the Br concentration in the desorption solution is more than 50 times that in the original high-halogen brine, and the enrichment factor is ≥50.
[0073] Beneficial effects:
[0074] This invention constructs a polyaniline composite material with high specific surface area, high oxidation state density, and a specific microstructure through nanofiberization and in-situ doping; the specific microstructure of the polyaniline composite material makes it resistant to Br. - It exhibits excellent selective adsorption, even in Br - very low concentration, Cl - Even in highly concentrated brine with a high concentration of chlorine and bromine, the Br content remains very high. - It exhibits excellent adsorption performance, high adsorption capacity, and maintains good selective adsorption, enabling the adsorption of low Br⁻ from... - Large-scale adsorption and extraction of Br in high-concentration brine - This increases yield; and it itself becomes a "microreactor," possessing catalytic oxidation properties, which can be combined with oxidants or electrolytic oxidation to... - Catalytic oxidation to elemental bromine is performed, and simultaneously, elemental bromine desorbs from the polyaniline composite material, thereby activating the polyaniline composite material and enabling its recycling. The polyaniline composite material, in conjunction with an oxidant or electrolytic oxidation, can effectively oxidize Br-... -> 15 g Br2 / (kg·h).
[0075] The present application does not need to use an oxidant to oxidize Br - in high-halogen salt water into bromine monomer in advance, but can directly use high-halogen salt water as raw material, adsorb Br - in large amounts by using polyaniline composite material, and realize catalytic oxidation and desorption by an oxidant or electrolytic oxidation to prepare bromine monomer, so that the preparation period is greatly shortened, the preparation process is simplified, the yield of bromine monomer is high, the whole process flow is short, the energy consumption is low, there is no strong acid and alkali waste liquid, the production cost of bromine is reduced to below 7700 yuan / ton, and the present application is suitable for complex high-salt brine systems such as seawater, tail water of seawater desalination, brine well, salt lake brine, and by-product water of potassium fertilizer mine.
[0076] The present application constructs a specific microstructure with high specific surface area and high oxidation state density through nanofiberization and in-situ doping, so that it itself becomes a “microreactor”, directly uses high-halogen salt water as raw material, adsorbs Br - in large amounts, and synchronously oxidizes and desorbs to realize synchronous preparation of bromine monomer and activated polyaniline composite material, fills the technical gap in the bromine production industry, and provides a novel industrialized method for extracting bromine from high-halogen salt water. BRIEF DESCRIPTION OF DRAWINGS
[0077] Figure 1 SEM image of the polyaniline composite material prepared in Example 1.
[0078] Figure 2 UV spectrum of the standard solution of Br3 - .
[0079] Figure 3 Standard curve of Br3 - .
[0080] Figure 4 Typical photo of the desorption solution of Example 1.
[0081] Figure 5 Br - adsorption capacity results of the polyaniline composite material of Example 1 and Comparative Example 3 on different Br - concentration tail water of seawater desalination, wherein PANI is Comparative Example 3, and PANI+Charcoal is Example 1.
[0082] Figure 6 Br - adsorption capacity results of the polyaniline composite material of Example 1 and Comparative Example 3 at different temperatures, wherein PANI is Comparative Example 3, and PANI+Charcoal is Example 1.
[0083] Figure 7The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3. - The results of the adsorption amount of Example 1 and Comparative Example 3, wherein PANI is Comparative Example 3 and PANI+Charcoal is Example 1.
[0084] Figure 8 The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3. - The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3.
[0085] Figure 9 The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3. - The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3.
[0086] Figure 10 The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3. - The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3. - The results of the concentration of Br3- in the desorption solution of the polyaniline composite material of Example 1 and Comparative Example 3 at different elution temperatures, wherein PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3. DETAILED DESCRIPTION
[0087] The technical solutions of the present application will be described in detail below through specific examples, but it should be clear that these examples are used for illustration, but not to be interpreted as limiting the scope of the present application.
[0088] Examples 1-7 and Comparative Examples 1-3
[0089] A preparation method of a polyaniline composite material, comprising the following steps: uniformly mixing a carrier, iron powder with a particle size of 0.2 mm and aniline, standing at room temperature, dropping 0.5 mol / L ammonium persulfate aqueous solution at a speed of 1 drop / s at room temperature, carrying out polymerization reaction while dropping, then filtering, washing with water and drying to obtain the polyaniline composite material.
[0090] The amount of each substance and the reaction conditions in Examples 1-7 and Comparative Examples 1-3 are shown in Table 1, respectively.
[0091] Table 1 Reaction conditions of Examples 1-7 and Comparative Examples 1-3
[0092]
[0093]
[0094] The above-mentioned activated carbon cylinder, graphene aerogel, carbon nanofiber film, zeolite, MOF-5, COF-1, and ZIF-8 can be purchased from the market.
[0095] The polyaniline composite material prepared in Example 1-7 was detected, and it was found that the iron was uniformly distributed on the surface of the carrier, the surface of the iron had a Fe2O3 layer, the polyaniline coated the carrier and the iron, and the polyaniline was in the form of nanofibers, the surface of the nanofiber was rough, the surface had villiform protrusions, the nanofibers were interlaced with each other, and the polyaniline was in the form of PANI + ; the length of the nanofiber was 1-10 μm, and the diameter was 10-100 nm; and the specific surface area of the polyaniline composite material was 300-1200 m 2 / g.
[0096] A typical SEM image thereof is shown in Figure 1 . Figure 1 The SEM image of the polyaniline composite material prepared in Example 1 is shown in
[0097] As can be seen from Figure 1 , the polyaniline composite material was in the form of nanofibers, the surface of the nanofiber was rough, the surface had granular protrusions, and the nanofibers were interlaced with each other; the length of the nanofiber was 3-7 μm, and the diameter was 60-80 nm.
[0098] Experiment 1
[0099] The composite materials prepared in Examples 1-7 and Comparative Examples 1-3 were taken out, and were respectively filled into chromatographic columns with the same size, and then the same volume of seawater desalination tail water (Cl - concentration was 50000 ppm, and Br - concentration was 80 ppm) was respectively added at room temperature, the effluent was collected, and the Cl - and Br - concentrations in the effluent were detected, and the adsorption amount of Cl - and Br - of each group of composite materials was calculated, and the results are shown in Table 2.
[0100] The adsorption amount = (initial ion concentration - ion concentration after adsorption) * solution volume / adsorbent mass.
[0101] Table 2: Ion adsorption amount results of Examples 1-7 and Comparative Examples 1-3
[0102]
[0103] As can be seen from Table 2, when the concentration ratio of Cl - and Br - in seawater was 625:1, the Br -The adsorption amount is much higher than that of the comparative examples 1-3, and much higher than that of the existing adsorbents (the existing adsorbents can adsorb Br - - The adsorption amount of the high-halogen salt water with a concentration lower than 300 ppm is low, and the existing adsorbents generally treat the solution with a Br - concentration higher than 300 ppm), and the polyaniline composite material has good adsorption of Br - .
[0104] Experiment 2
[0105] Sodium bromide standard was taken, and solutions with different concentration gradients were prepared, and equal amounts of saturated ammonium persulfate aqueous solution (citric acid was used to adjust pH = 2.0) were added, and stirring was performed for 10 min for oxidation, and the filtrate was taken as Br3 - standard solution with different concentration gradients, and the ultraviolet absorbance of each Br3 - standard solution was detected at 330 nm, and a standard curve was drawn, and the results are shown in Figures 2-3 .
[0106] Figure 2 It is the ultraviolet spectrum of the Br3 - standard solution with different concentration gradients.
[0107] Figure 3 It is the standard curve of Br3 - .
[0108] The composite materials after adsorption in each group in experiment 1 were taken, and equal amounts of eluent (the eluent was saturated ammonium persulfate aqueous solution, and citric acid was used to adjust pH = 2.0) were added to the column, and the flow rate was controlled to be 1 ml / min for elution; the eluate was collected, the absorbance of each group of eluate was detected at 330 nm, and the concentration of Br3 - in each group of eluate was calculated according to the standard curve, and the results are shown in Table 3 and Figure 4 .
[0109] Figure 4 It is a typical photo of the eluate of example 1.
[0110] Table 3 concentration of Br3 - in the eluate of examples 1-7 and comparative examples 1-3
[0111]
[0112] As can be seen from Table 3, after treatment with the eluent, more Br3 - can be obtained in examples 1-7, which shows that the polyaniline composite material and the antioxidant can cooperate to adsorb Br - The catalytic oxidation of Br- to Br3, and the desorption of Br3 from the polyaniline composite material, thus realizing the activation of the polyaniline composite material and its recycling; while the Br3 obtained from Comparative Examples 1-3 after treatment with the eluent is - Less, far lower than that of Examples 1-7.
[0113] Experiment 3
[0114] The polyaniline composite material of Example 1 was taken, and the concentration of Br3 in the desorption liquid was detected according to the method of Experiment 2, wherein ammonium persulfate was replaced by oxygen, ozone, potassium permanganate, chlorine, and citric acid was replaced by malic acid, tartaric acid, oxalic acid, and benzoic acid, and the results are shown in Table 4. -
[0115] Table 4 Concentration of Br3 prepared by different eluents -
[0116] Eluate Br3 - concentration ppm Oxidant was oxygen, organic acid was malic acid, pH was 3 1990 Oxidant was ozone, organic acid was tartaric acid, pH was 1 1998 Oxidant was potassium permanganate, organic acid was oxalic acid, pH was 2 2018 Oxidant was chlorine, organic acid was benzoic acid, pH was 2 2010
[0117] As can be seen from Table 4, the oxidants oxygen, ozone, potassium permanganate, chlorine, and the organic acids malic acid, tartaric acid, oxalic acid, and benzoic acid can also cooperate with the polyaniline composite material to catalytically oxidize Br- to Br3. -
[0118] Experiment 4
[0119] The polyaniline composite materials of Example 1 and Comparative Example 3 were taken and filled into chromatographic columns respectively, and the adsorption amount (unit: mg / g) of Br- in different concentrations of Br- in seawater desalination tail water was investigated; the results are shown in Table 5. - - Figure 5
[0120] Figure 5 The results of the adsorption amount of Br- in seawater desalination tail water of different concentrations of Br- by the polyaniline composite materials of Example 1 and Comparative Example 3, wherein PANI is Comparative Example 3, and PANI+Charcoal is Example 1. - -
[0121] As can be seen from Table 6, with the increase of the concentration of Br-, the adsorption amount of Br- of Example 1 and Comparative Example 3 gradually increased, but the adsorption amount of Example 1 was much higher than that of Comparative Example 3. Figure 5 - -
[0122] The polyaniline composite materials of Example 1 and Comparative Example 3 were taken and filled into chromatographic columns respectively, and seawater desalination tail water (Cl- concentration of 50000 ppm, Br- concentration of 100 ppm) was loaded; the results are shown in Table 7. - - The effect of a concentration of 80 ppm on Br at different temperatures was investigated. - The adsorption capacity (in mg / g); the results are as follows Figure 6 As shown.
[0123] Figure 6 The polyaniline composites of Example 1 and Comparative Example 3 were tested at different temperatures for the effect of Br... - The adsorption results are shown in the figures, where PANI is the comparative example 3 and PANI+Charcoal is the example 1.
[0124] Depend on Figure 6 It can be seen that: with increasing temperature, the Br in Example 1 and Comparative Example 3... - The adsorption amount gradually decreased, and the decrease in Example 1 was greater than that in Comparative Example 3.
[0125] The polyaniline composite materials from Example 1 and Comparative Example 3 were respectively packed into chromatography columns, and then seawater desalination tailwater (Cl) was loaded onto the columns at room temperature. - The concentration is 50,000 ppm, Br - (Concentration 80 ppm), adjust different flow rates, collect the effluent, and detect the Br in the effluent. - Concentration, calculation of the effect of polyaniline composite material on Br at different flow rates - The adsorption amount (in ppm) is as follows: Figure 7 As shown.
[0126] Figure 7 The polyaniline composite materials of Examples 1 and 3 were tested at different flow rates for Br. - The adsorption results are shown in the figures, where PANI is the comparative example 3 and PANI+Charcoal is the example 1.
[0127] Depend on Figure 7 It can be seen that: with the increase of flow rate, the Br in Example 1 and Comparative Example 3... - The adsorption amount gradually decreased, and the decrease in Example 1 was greater than that in Comparative Example 3.
[0128] The polyaniline composite materials from Example 1 and Comparative Example 3 were respectively packed into chromatography columns, and then seawater desalination tailwater (Cl) was loaded onto the columns at room temperature. - The concentration is 50,000 ppm, Br - (Concentration of 80 ppm) was used for Br - Adsorption was performed, followed by elution with eluent (saturated ammonium persulfate aqueous solution, pH adjusted to 2.0 with citric acid) at different temperatures and a flow rate of 1 ml / min. The desorbed solutions were collected, and the absorbance of each group of desorbed solutions was measured at 330 nm. The Br3 content in each group of desorbed solutions was calculated according to the standard curve. -The concentration (i.e., the amount of bromine desorbed, in ppm) was as follows: Figure 8 As shown.
[0129] Figure 8 For the polyaniline composite materials of Example 1 and Comparative Example 3, the Br3 content in the desorption solution was measured at different elution temperatures. - The concentration results are as follows, where PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3.
[0130] Depend on Figure 8 It can be seen that as the elution temperature increases, the amount of bromine desorbed in Example 1 gradually increases; while the amount of bromine desorbed in Comparative Example 3 does not change significantly.
[0131] The polyaniline composite materials from Example 1 and Comparative Example 3 were respectively packed into chromatography columns, and then seawater desalination tailwater (Cl) was loaded onto the columns at room temperature. - The concentration is 50,000 ppm, Br - (Concentration of 80 ppm) was used for Br - Adsorption was performed, followed by elution with an eluent (a saturated ammonium persulfate aqueous solution adjusted to pH 2.0 with citric acid) at different flow rates. The desorbed solutions were collected, and the absorbance of each group was measured at 330 nm. The Br3 concentration in each group was calculated according to a standard curve. - The concentration (i.e., the amount of bromine desorbed, in ppm) was as follows: Figure 9 As shown.
[0132] Figure 9 For the polyaniline composite materials of Example 1 and Comparative Example 3, the Br3 content in the desorption solution was measured at different elution rates. - The concentration results are as follows, where PANI+Charcoal / Cit / APS is Example 1 and PANI / Cit / APS is Comparative Example 3.
[0133] Depend on Figure 9 It can be seen that as the elution rate increases, the amount of bromine desorbed in Example 1 and Comparative Example 3 gradually decreases; the decrease in Example 1 is greater than that in Comparative Example 3.
[0134] Experiment 5
[0135] Method A: Take the polyaniline composite material from Example 1, pack it into a chromatography column, and then load it with different Br at room temperature. - Concentration of seawater desalination tailwater (of which Cl) -After adsorption saturation (at a concentration of 50,000 ppm), the solution was eluted with eluent (a saturated ammonium persulfate aqueous solution adjusted to pH 2.0 with citric acid) at a flow rate of 1 ml / min. The desorbed solutions were collected, and the absorbance of each group was measured at 330 nm. The Br3 concentration in each group of desorbed solutions was calculated according to the standard curve. - The concentration (i.e., the amount of bromine desorbed, in ppm) was as follows: Figure 10 As shown.
[0136] Method B: Take the polyaniline composite material from Example 1 and add different Br... - Concentration of seawater desalination tailwater (of which Cl) - After adsorption saturation in a solution of 50,000 ppm, the sample was removed and used as the positive electrode, with Pt as the negative electrode. The sample was then immersed in a citric acid aqueous solution at pH 2, and a voltage of 0.8 V was applied for 10 minutes. The voltage was then turned off to obtain the desorbed solution. The absorbance of each desorbed solution was measured at 330 nm, and the Br3 concentration in each desorbed solution was calculated according to the standard curve. - The concentration (i.e., the amount of bromine desorbed, in ppm) was as follows: Figure 10 As shown.
[0137] Figure 10 To use different Br - When preparing elemental bromine from seawater desalination tailwater of a certain concentration, the Br3 in the desorption solution... - The concentration results are as follows: PANI+Charcoal / Cit / APS is for method A, and electrolysis is for method B.
[0138] Depend on Figure 10 It can be seen that the higher the concentration of bromide ions in seawater, the more bromine Br3 is desorbed. - The more; electrolysis (method B) is slightly superior to chemical oxidation (method A) in the preparation of Br3. - .
[0139] Experiment 7
[0140] The polyaniline composite material from Example 1 was used to prepare bromine at 25°C according to methods A and B in Experiment 6. Both were recycled 200 times. It was found that after 200 cycles, the activity (adsorption performance and catalytic oxidation performance) of the polyaniline composite material in method A decreased by less than 10%, while the activity of the polyaniline composite material in method B remained basically unchanged.
[0141] The desorbed liquids obtained by methods A and B above can be used to blow out bromine vapor with hot air, and then condensed to obtain liquid bromine.
[0142] In method A above, ammonium persulfate in the desorption solution is converted into ammonium sulfate after catalytic oxidation, which can be recycled and used as fertilizer.
[0143] The above description is only the preferred embodiment of the present application, but the protection scope of the present application is not limited to this. Any person skilled in the art can make equivalent replacements or changes according to the technical solution and the inventive concept of the present application within the technical range disclosed by the present application, which should be covered in the protection scope of the present application.
Claims
1. A polyaniline composite material, characterized in that, include: The components are a carrier, iron, and polyaniline. The iron has an Fe2O3 layer on its surface and is uniformly distributed on the surface of the carrier. The polyaniline coats the carrier and the iron and is in the form of nanofibers.
2. The polyaniline composite material according to claim 1, characterized in that, The nanofibers have fluffy protrusions on their surface; preferably, the nanofibers are interwoven; preferably, the polyaniline in the polyaniline composite material is PANI. + The nanofibers are preferably 1-10 μm long and 10-100 nm in diameter; preferably, the nanofibers are 3-7 μm long and 50-90 nm in diameter.
3. The polyaniline composite material according to claim 1 or 2, characterized in that, The specific surface area of polyaniline composites is 300-1200 m². 2 / g; preferably, the iron particle size is 0.1-0.5mm.
4. The polyaniline composite material according to any one of claims 1-3, characterized in that, The carrier has adsorption properties; preferably, the specific surface area of the carrier is ≥300 m². 2 / g; Preferably, the support has a porous structure and / or a layered structure; Preferably, the support includes one or more of the following: porous materials, graphene, carbon nanotubes, and layered double hydroxides; Preferably, the porous material includes one or more of the following: one-dimensional porous materials, two-dimensional porous materials, and three-dimensional porous materials; Preferably, the porous material includes one or more of the following: porous carbon fibers, porous carbon particles, porous carbon cloth, porous carbon felt, molecular sieves, porous silicon fibers, porous silicon particles, porous silica fibers, porous silica particles, porous titanium dioxide fibers, porous titanium dioxide particles, porous ceramics, aerogels, and sponges; Preferably, when the support has a porous structure, the pore size is 0.3-100 nm.
5. A method for preparing the polyaniline composite material according to any one of claims 1-4, characterized in that, The process includes the following steps: mixing the carrier, iron powder and aniline, letting it stand, adding an initiator solution to carry out a polymerization reaction, and obtaining a polyaniline composite material.
6. The method for preparing the polyaniline composite material according to claim 5, characterized in that, The weight ratio of carrier, iron powder, and aniline is 100:0.001-0.5:0.5-10; preferably, the weight ratio of aniline and initiator is 1:0.8-1.5; preferably, the concentration of the initiator solution is 0.1-3 mol / L.
7. The method for preparing the polyaniline composite material according to claim 5 or 6, characterized in that, The mixture is allowed to stand at room temperature for 1-5 hours; preferably, the polymerization reaction is carried out at room temperature; preferably, after standing, an initiator solution is added dropwise to carry out the polymerization reaction; preferably, the dropping rate is 1-2 drops / s.
8. The application of a polyaniline composite material as described in any one of claims 1-4, or a polyaniline composite material prepared by the method as described in any one of claims 5-7, in the selective adsorption of bromide ions and in the catalytic oxidation preparation of elemental bromine; preferably, its application in the selective adsorption of bromide ions in high-halogen brine; preferably, the application of Br in high-halogen brine... - The concentration is ≤300ppm; preferably, the concentration ratio of chlorine to bromine in the high-brine brine is 600-7500:1; preferably, the high-brine brine is one of seawater, seawater desalination tailwater, salt lake brine, deep well brine, or potash fertilizer mine by-product water; preferably, bromine is prepared by catalytic oxidation in an acidic environment; preferably, the pH of the acidic environment is ≤3; preferably, the acidic environment is maintained by an organic acid; preferably, the organic acid is one or more of formic acid, acetic acid, propionic acid, butyric acid, lactic acid, citric acid, malic acid, tartaric acid, oxalic acid, benzoic acid, salicylic acid, phthalic acid, terephthalic acid, acrylic acid, methacrylic acid, sorbic acid, fumaric acid, maleic acid, succinic acid, and glutaric acid.
9. A method for preparing elemental bromine from high-salinity brine, characterized in that, Including method A or method B, Method A includes the following steps: adsorbing bromine from high-salt brine using a polyaniline composite material, then eluting the adsorbed bromine from the polyaniline composite material with an eluent to obtain a desorption solution; blowing bromine vapor out of the desorption solution and condensing it to obtain liquid bromine. Method B includes the following steps: using a polyaniline composite material to adsorb bromine from high-salt brine, then using the bromine-adsorbed polyaniline composite material as a positive electrode, performing electrolytic desorption in an acidic aqueous solution to obtain a desorbed solution; blowing bromine vapor out of the desorbed solution and condensing it to obtain liquid bromine. In Method A, the eluent is an acidic aqueous solution containing an oxidizing agent; The polyaniline composite material is the polyaniline composite material described in any one of claims 1-4 or the polyaniline composite material prepared by the method described in any one of claims 5-7.
10. The method for preparing elemental bromine from high-salinity brine according to claim 9, characterized in that, In method A, the pH of the eluent is ≤3; preferably, in method A, the oxidant is one or more of oxygen, ozone, potassium permanganate, nitric acid, concentrated sulfuric acid, persulfate, hydrogen peroxide, sodium peroxide, sodium hypochlorite, calcium hypochlorite, chlorine, potassium dichromate, lead dioxide, chromium trioxide, perchloric acid, periodic acid, osmium tetroxide, and sodium dichloroisocyanurate; preferably, in method B, the pH of the acidic aqueous solution is ≤3; preferably, in method B, the voltage of electrolysis is ≤1.2V.